Unlocking the structure-property relationships of conjugated polyelectorlytes and photoactive surfactants to design functional responsive materials - Houston, Judith E. (Trinity College (Dublin, Ireland). School of Chemistry, 2017)
Self-assembly is an elegant method for the preparation of functional responsive materials. This thesis focuses on understanding the self-assembly properties of photoactive soft matter systems (e.g. polymers, polyelectrolytes, phospholipids, liquid crystals). The goal has been to identify key structure-property relationships that facilitate the rational design of functional materials for organic solar cells, bio-imaging and bio-sensing platforms. Conjugated polyelectrolytes (CPEs) have shown promise in a range of applications from optical sensors to organic photovoltaic devices (OPVs), due to their exceptional optoelectronic properties, low cost and solution processability. Chapters 4-6 focus on exploiting different solvents and counter-ions to modulate the aggregated structure of CPEs in solution, and the subsequently prepared thin films, for use as interfacial layers in OPVs. Specifically, the ability to tune the nanoscale organisation of aggregates of amphiphilic diblock copolymers in solution via solvent and surfactant mediation is shown to be a simple and effective method to control the film morphology. Furthermore, the incorporation of poly(thiophene)-surfactant complexes as a cathodic interfacial layers in OPV devices resulted in a 20% increase in the power conversion efficiency.
Keywords: Chemistry, Ph.D.; PhD Trinity College Dublin, 2017